Temperature-Dependent Influence of FliA Overexpression on PHL628 E. coli Biofilm Growth and Composition - Buck, Luke D.; Paladino, Maddison M.; Nagashima, Kyogo; Brezel, Emma R.; Holtzman, Joshua S.; Urso, Sarel J.; Ryno, Lisa M. (Frontiers in Cellular and Infection Microbiology, 2021)
Biofilm growth and survival pose a problem in both medical and industrial fields. Bacteria in biofilms are more tolerant to antibiotic treatment due to the inability of antibiotics to permeate to the bottom layers of cells in a biofilm and the creation of altered microenvironments of bacteria deep within the biofilm. Despite the abundance of information we have about E. coli biofilm growth and maturation, we are still learning how manipulating different signaling pathways influences the formation and fitness of biofilm. Understanding the impact of signaling pathways on biofilm formation may narrow the search for novel small molecule inhibitors or activators that affect biofilm production and stability. Here, we study the influence of the minor sigma transcription factor FliA (RpoF, sigma-28), which controls late-stage flagellar assembly and chemotaxis, on biofilm production and composition at various temperatures in the E. coli strain PHL628, which abundantly produces the extracellular structural protein curli. We examined FliA’s influence on external cellular structures like curli and flagella and the biomolecular composition of the biofilm’s extracellular polymeric substance (EPS) using biochemical assays, immunoblotting, and confocal laser scanning microscopy (CLSM). At 37°C, FliA overexpression results in the dramatic growth of biofilm in polystyrene plates and more modest yet significant biofilm growth on silica slides. We observed no significant differences in curli concentration and carbohydrate concentration in the EPS with FliA overexpression. Still, we did see significant changes in the abundance of EPS protein using CLSM at higher growth temperatures. We also noticed increased flagellin concentration, a major structural protein in flagella, occurred with FliA overexpression, specifically in planktonic cultures. These experiments have aided in narrowing our focus to FliA’s role in changing the protein composition of the EPS, which we will examine in future endeavors.